USE BORDA ANALYSIS TO DETERMINE THE PRIORITY OF THE INDONESIAN NAVAL TECHNOLOGY COLLEGE DEVELOPMENT STRATEGY - Ayip Rivai Prabowo; Zaenal Fanani; Moeljadi Moeljadi; Tjahjanulin Domai (JOURNAL ASRO, 2019)
The Indonesia Naval Technology College requires an organizational development strategy in order to produce professional student outcomes and master maritime technology. Based on this, we can choose the priority of development strategies by weighting based on expert choices. The problem in this research is how to determine the priority of strategies that can be implemented in the development of the Indonesian Naval Technology College. The purpose of this research is to weight some strategies in developing the Indonesian Naval Technology College. In this study, the SWOT analyst and Borda Analysis methods are used to determine the assessment of the strategy. The results of the study indicate that to be able to improve the professionalism of soldiers in the fields of science and technology, it is necessary to increase the quantity and quality of complete laboratory infrastructure facilities, publication of lecturer and student research in national and international journals, Changes in the structure of the ideal Indonesian Naval Technology college will be able to support operational education and development of new study programs and the regulation of curriculum changes in each study programs that leads to the field of science and technology in the rank of marine. Keywords: The Indonesian Naval Technology College, SWOT Analysis, Borda Analysis, Development Strategy.